Propuesta de un plan estratégico para la Empresa Portugal M.H. de Seguridad Privada Cía. Ltda. ubicada en la ciudad de Riobamba provincia de Chimborazo - Silva Portugal, Fredy Dario (2015)
This thesis project consists in developing a strategic plan for the company MH PORTUGAL PRIVATE SECURITY CO. LTDA. Located in the city of Riobamba, Chimborazo province that would promote the development and growth of the organization covered by this study, which was carried out based on theoretical underpinnings and field information obtained by employing customer surveys 22, 71 employees and an interview with the manager. The process of investigating this issue, some from making a situational analysis of the company. Upon surveys of customers and employees, the interview the manager and direct observation, gave us an overview of current business conditions and their social environment. For this first external analysis was performed in the company, which allowed us to define the opportunities and threats of the same, so the EFE matrix, wherein the weighted total is 2.40 was constructed, indicating that the weight of the opportunities is greater than the impact of threats. Then by internal analysis of the company a diagnosis of it was conducted, whereby the strengths and weaknesses are determined, and thus the EFI matrix gave us the weighted score 2.4 was developed, which means that the company is weak internally. With internal and external analysis SWOT matrix that allowed us to define the opportunities, threats, strengths and weaknesses, which the matrix high impact with what we proceeded to perform the FO, DO, FA combination was built was built, DA resulting in strategic objectives. The definition of strategic objectives a strategic plan for the company MH was developed PORTUGAL PRIVATE SECURITY CO. LTDA. Located in the city of Riobamba, Chimborazo province, which will serve for the organization to capture new customers, improve the service provided to its customers and generate higher returns for its members. Finally, we define the main conclusions that we arrived after finishing the research